Pengaruh Faktor Sosial terhadap Intensi Bermain Judi Online: Peran Moderasi Kecerdasan Emosional - Sadikin, Sadikin (JURNAL SOSIAL HUMANIORA (JSH), 2025)
This study investigates the prevalence of online gambling and its significant impact on individuals, with many falling victims to its addictive nature. A cross-sectional study design was employed, focusing on a population of active online gambling players. The sample was selected using probability sampling, and the sample size was calculated using an indicator formula multiplied by five observations, resulting in 135 respondents. Data analysis involved descriptive statistical methods and Structural Equation Modeling (SEM) to explore the relationships among variables. The findings highlight those psychological factors, such as stress and impulsiveness, significantly influence the intensity of online gambling behavior. Furthermore, emotional intelligence was identified as a critical mediator, moderating the link between psychological factors and gambling intensity. Individuals with higher emotional intelligence demonstrated better control over their gambling habits, even when exposed to adverse psychological conditions. These results underscore the complex interplay between psychological well-being and emotional regulation in shaping gambling behavior. The study emphasizes the need for targeted interventions, such as emotional intelligence training, to mitigate the negative impact of psychological vulnerabilities and reduce the intensity of online gambling. Such strategies could provide valuable tools for addressing the growing issue of online gambling addiction